Imagining the future of global education dreams and nightmares - Zhao, Yong 1965-; Gearin, Brian (Routledge, Taylor & Francis Group, 2018)
"Imagining the Future of Global Education examines the Grand Education Narrative (GEN) and the major institutions that shape and disseminate it. The focus is on national visions and imaginary futures that nations seek to make reality, with a critique of the GEN policy implementation process that turns dreams of upward mobility of education into nightmares. In this way, the book takes a distinctly different approach than most comparative and international education studies which are oriented toward the past and ask how education systems around the world ended up where they are. Rather, the chapters in this volume investigate imagined futures, good and bad, and seek an understanding of how those educational visions inform the present and shape the future. Following an introductory summary of important concepts from scholarship on global education reform and futurology, the book is organized around three themes: "What Dreams are Made Of," illustrating, through three case studies, what the GEN looks like at the national level and how it operates across national boundaries; "A Dream within a Dream" considering some of the more novel trends in international education reform in order to provide insight into how dreams seem to function; and "Keeping Dreams from becoming Nightmares" comprising three thematic essays that describe trends in education policy in one or more countries" ...
Includes bibliographical references and index
Keywords: International education -- Cross-cultural studies; Education and globalization -- Cross-cultural studies; Economic development -- Effect of education on -- Cross-cultural studies; Chancengleichheit; Internationaler Vergleich; Bildungspolitik; Bildungsreform